PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Dwi Fitrianingsih; Siti Asfaro (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine "The Impact of Good Corpoorate Governance to Financial Performance on basic banking companies in Indonesia Stock Exchange". Data collection techniques used purposive sampling and the number of samples in this study were 50 data. From the results with partial test (t) use return on asset (ROA) the board of directors has a positive and insignificant effect on financial performance of return on asset (ROA), board of commissioners has a positive and not significant effect on financial performance of return on asset (ROA), audit committee does not significantly influence financial performance return on asset, good corporate governance has no significant effect on financial performance return on asset (ROA). From the results with partial test (t) use return on equity (ROE) the board of directors has a positive and insignificant effect on financial performance of return on equity (ROE), board of commissioners does not have a significant effect on financial performance on return on equity (ROE), audit committee does not have a significant effect on financial performance return on equity (ROE), good corporate governance has no significant effect on financial performance return on equity (ROE).